Transparansi, Partisipasi dan Akuntabilitas Pengelolaan Dana Desa Tahun 2023 di Desa Gurung Turi Kabupaten Manggarai Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is entitled Transparency, Participation and Accountability of Village Fund Management in 2023 in Gurung Turi Village, East Manggarai Regency. The purpose of the research is to find out the management of Village Funds in 2023 in Gurung Turi Village. The method used is a qualitative method. This study examines the management of Village Funds and their management using 3 important aspects, namely; principles of transparency, participation and accountability. The results of the study show that the management of village funds seen in terms of transparency is constrained by the closure of information systems through information media such as billboards, websites and village bulletin boards. In addition, decision-making is considered to be still closed, where decision-making is only held by the village government. The active involvement and low supervision by the Gurung Turi Village Community in the management of village funds affects the low accountability delivery mechanism that is not transparent and effective to the community as well as obstacles that result in the village government carrying out its duties and functions not in accordance with existing regulations.